Equivalent-Small-Parameter Analysis of DC/DC Switched-Mode Converter - Chen, Yanfeng; Zhang, Bo.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the applications of Equivalent-Small-Parameter Method (ESPM) in solving the steady-state periodic solutions, as well as stability analysis, of kinds of open-loop or closed-loop operated DC/DC converters, such as PWM, quasi-resonant and resonant ones. The analytical expressions of DC components and harmonics of state variables (inductor current and capacitor voltage) with DC/DC converters can be obtained by ESPM, which can be helpful to understand the nonlinear operating mechanism of switched-mode converters. It can also be useful for stability analysis and design for practical converters. Modeling and analysis on all kinds of DC/DC converters are introduced in detail in this book, along with a large amount of simulation or experimental waveforms to verify the correctness of the theoretical analysis based on ESPM.
Introduction -- Review on Modeling and Analysis Methods of Switched-mode Converter -- A General Nonlinear Mathematical Model of DC/DC Converters -- Equivalent-Small-Parameters Method (ESPM) -- Modeling and Analysis of Open-loop PWM DC/DC Converters Based on ESPM -- Modeling and Analysis of Voltage-mode Controlled PWM DC/DC Converters Based on ESPM -- Modeling and Analysis of Current-mode Controlled PWM DC/DC Converters Based on ESPM -- Modeling and Analysis of PFM Quasi-Resonant DC/DC Converters Based on ESPM -- Stability Analysis of DC/DC Converters Based on ESPM -- Summary.
Keywords: Electronic circuits; Electric power production; System theory; Control theory; Electronic Circuits and Systems; Electrical Power Engineering; Systems Theory, Control